Determinação do perfil de compostos voláteis e avaliação do sabor e aroma de bebidas produzidas a partir da erva-mate (Ilex paraguariensis) - Machado, Carla Carolina Batista; Bastos, Deborah Helena Markowicz; Janzantti, Natália Soares [UNESP]; Facanali, Roselaine; Marques, Marcia Ortiz M.; Franco, Maria Regina Bueno (Sociedade Brasileira de Química, 2007)
Volatile compounds from green and roasted yerba mate were analyzed by gas chromatography/mass spectrometry and the flavor profile from yerba mate beverages was determined by descriptive quantitative analyses. The main compounds tentatively identified in green mate were linalool, alpha-terpineol and trans-linalool oxide and in roasted mate were (E,Z)-2,4-heptadienal isomers and 5-methylfurfural. Green mate infusion was qualified as having bitter taste and aroma as well as green grass aroma while roasted mate was defined as having a smooth, slightly burnt aroma. The relationship between the tentatively identified compounds and flavor must be determined by olfatometric analysis.
Volatile compounds profile and flavor analysis of yerba mate (Ilex paraguariensis) beverages
Keywords: yerba mate; volatile compounds; flavor